2017
DOI: 10.1016/j.aim.2017.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Heisenberg uniqueness pairs for some algebraic curves in the plane

Abstract: Abstract. A Heisenberg uniqueness pair is a pair (Γ, Λ), where Γ is a curve and Λ is a set in R 2 such that whenever a finite Borel measure µ having support on Γ which is absolutely continuous with respect to the arc length on Γ satisfiesμ| Λ = 0, then it is identically 0. In this article, we investigate the Heisenberg uniqueness pairs corresponding to the spiral, hyperbola, circle and certain exponential curves. Further, we work out a characterization of the Heisenberg uniqueness pairs corresponding to four p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…In a recent article [22], the second author has shown that a cone is a Heisenberg uniqueness pair corresponding to sphere as long as the cone does not completely lay on the level surface of any homogeneous harmonic polynomial on R n . Thereafter, a sense of evidence emerged that the exceptional sets for the HUPs corresponding to the sphere are eventually contained in the zero sets of the spherical harmonics and the Bessel functions, though we yet resolve it (see [6,22]).…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…In a recent article [22], the second author has shown that a cone is a Heisenberg uniqueness pair corresponding to sphere as long as the cone does not completely lay on the level surface of any homogeneous harmonic polynomial on R n . Thereafter, a sense of evidence emerged that the exceptional sets for the HUPs corresponding to the sphere are eventually contained in the zero sets of the spherical harmonics and the Bessel functions, though we yet resolve it (see [6,22]).…”
Section: Introductionmentioning
confidence: 96%
“…Subsequently, Babot [2] has given a characterization of the Heisenberg uniqueness pairs corresponding to a certain system of three parallel lines. Thereafter, the authors in [6] have given some necessary and sufficient conditions for the Heisenberg uniqueness pairs corresponding to a system of four parallel lines. However, an exact analogue for the finitely many parallel lines is still unsolved.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the case of circle and parabola were studied by Nir Lev [6] and Per Sjölin [8] respectively. Please see [2], [4], [7], [9] and [10] for more results in this direction.…”
Section: Introductionmentioning
confidence: 99%